Associations between Agility, the Relative Age Effect, Siblings, and Digit Ratio (D2:D4) in Children and Adolescents - Daniel González-Devesa; Alba López-Eguía; Lucas Amoedo; Carlos Ayán-Pérez (MDPI AG, 2024)
Background: This study aims to analyze the influence of relative age effects, siblings, and digit ratio on the agility of children and adolescents. Methods: The study included 283 children (9.54 ± 1.36 years) and 296 adolescents (14.68 ± 1.36 years) from four different schools. The analyzed variables included anthropometric data, the presence of siblings, relative age effect, and results from the 10 × 5 m shuttle run test. Results: The findings indicated no significant association between agility and either the 2D:4D ratio or the relative age effect in both children and adolescents (p > 0.05). Additionally, having siblings did not have a notable impact on agility. Multiple regression analysis confirmed that relative age did not influence this lack of association (quarter of birth: p = 0.345, β = 0.039; siblings: p = 0.100, β = −0.069). However, boys showed higher performance than girls in the 10 × 5 m shuttle run test, and higher body mass index was related to lower agility. Conclusions: These findings contribute to existing knowledge on the relative effects of age and provide valuable information for physical education teachers on the influence of the 2D:4D ratio and the presence of siblings on the physical fitness of children and adolescents.